Vegetación y flora de un ecotono entre las provincias del altilpano y de la planicie costera del noreste de México - Briones, Oscar; Villarreal Q., J. A. (Instituto de Ecología, A.C., 2001)
The vegetation and the vascular plants of an ecotonal zone between the floristic provinces of the Desert Plateau (Chihuahuan Desert) and Gulf Coastal Plain in northeastern México were studied. The study zone has a surface of 2,526.25 km2 and it is located in the northern part of the state of Nuevo León. On the basis of physiognomy, ecological characteristics and dominant species, seven types of vegetation were recognized. With the aid of 50 sampling plots, aerial photographs and floristic composition, the units of vegetation were delimited and mapped. 405 species (varieties and subspecies included) were identified. The study zone showed geographical affinity with the vegetation of the Chihuahuan Desert in the Desert Plateau of México (Hilaria mutica grassland, low thornless scrub of Flourensia cernua and medium size mixed scrub of Acacia-Prosopis-Flourensia-Larrea) and with the Gulf Coastal Plain (medium size mixed scrub of Leucophyllum frutescens and Acacia rigidula and high mixed scrub of Helietta parvifolia). The medium size and high thorny scrubs of Prosopis-Acacia showed no clear relationships with any of the floristic provinces. The coexistence of shrubby vegetation characteristic of the lowlands in the Gulf Coastal Plain and the vegetation usually present in the Chihuahuan Desert, can be explained in view of the increment of aridity and gentle raising of the continental surface in east-west direction, and of the absence of notable topographic accidents in the northeastern region of México.